Pengaruh Arus Kas Operasi, Debt Covenant, Ukuran Perusahaan Dan Reputasi Kantor Akuntan Publik Terhadap Konservatisme Akuntansi : Studi Empiris Pada Perusahaan Sektor Consumer Non-Cyclicals Yang Terdaftar Pada Bursa Efek Indonesia Periode 2019 - 2023 - Dira Julinda Swasti; Rinny Meidiyustiani (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The purpose of the study is to determine and analyze the effect of Cash Flow Operation, Debt Covenant, Firm Size, and Public Accounting Firm Reputation on Conservatism Accountancy of consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2019- 2023. In this study, a purposive sampling method is used, which obtained 60 companies. The data analysis used in this study is multiple linear regression analysis using SPSS software version 22 and Microsoft Excel 2019. The results of this study indicate that cash flow operation and debt covenant have a positive significant effect on conservatism accountancy. At the same time, firm size have a negative significant effect on conservatism accountancy. Then, the public accounting firm reputation has no effect on conservatism accountancy.